EU competitiveness and the 2030 framework: A industry perpective. Final report referring to EASME/COSME/2014/031 - Claire Gavard; Sebastian Voigt (European Union, 2017)
With the EU 2020 climate and energy package and the 2030 framework, the European Union has set clear objectives to be on track to reduce its greenhouse gas emissions by 80% compared to 1990 levels by 2050. The objective of this work is to conduct a comparable analysis that takes account of EU climate energy and policy developments and recent Commission's proposals, including its 'Clean Energy for All Europeans' package (EC, 2016a) and its proposals for an Effort Sharing Regulation for the period 2021-2030 (EC, 2016d) and revised EU Emissions Trading System (EU ETS) (EC, 2015b), as well as international climate negotiations orientated towards the preparation of climate pledges for 2030 in the context of the Paris Agreement. The analysis is conducted with the PACE (Policy Analysis based on Computable Equilibrium) model. Four main policy scenarios are considered to examine the impact of the 2030 targets on the competitiveness of the EU's industrial sectors. They reflect two levels of action within the Paris Agreement (EU unilateral action vs. international action beyond 2020) and two ways of using the EU ETS auction revenues (lump-sum transfer to households vs. subsidies for Renewable Energy Sources (RES)). In addition, these four scenarios are also examined with some variants to analyse further the impact of different settings for RES support schemes in Member States (MS). Indeed, the model was developed to allow for different types of RES support, which can also be combined: RES public support paid by tax payers, electricity levy directed to RES support and paid by electricity users and RES subsidy financed by the auction revenues. In the four main scenarios, the RES support settings have been chosen to be as close as possible to the current situation in the different MS while in variant (1) RES support is assumed to be an electricity levy in all MS. In variant (2), RES support is also a levy everywhere in Europe but the ETS sectors are not exempted from the levy.
Keywords: 330